Le rôle de l'orientation syndicale des Chambres d'agriculture dans la contractualisation des mesures agro-environnementales - Florimond Brun (Éditions en environnement VertigO, 2014)
Agro-Environmental Schemes (AESs) aim at reducing the impact of farming on the environment. In practice, AESs have been implemented in a decentralized fashion, with a key role for farmers’ unions and their representatives elected to the Chambers of Agriculture (CA) in determining the level of transaction costs and windfall effects. We test the assumption that the relative strength of farmers’ unions has influenced the contracting of AESs in each French "department" between 2000 and 2006. In order to solve for the endogeneity problem, we use as an identification strategy the inclusion of control variables and also spatial differencing. Our results suggest that the vote for the National Federation of French Farmers’ Unions, the main farmers’ union at the time, has a positive effect on the contracting of AESs, but in favor of the schemes with the lowest environmental requirements.